2010
DOI: 10.1111/j.1750-3841.2009.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Shelf Life of Pasteurized Milk in Bottle and Pouch

Abstract: Shelf life of pasteurized milk in Brazil ranges from 3 to 8 d, mainly due to poor cold chain conditions that prevail throughout the country and subject the product to repeated and/or severe temperature abuse. This study evaluated the influence of storage temperature on the microbiological stability of homogenized whole pasteurized milk (75 degrees C/15 s) packaged in high-density polyethylene (HDPE) bottle and low-density polyethylene (LDPE) pouch, both monolayer materials pigmented with titanium dioxide (TiO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
1
30
1
3
Order By: Relevance
“…Control milk, therefore, reached cut-off values in less than 1 week, with aerobic microbiota counts of 104 CFU ml-1 when held at 4°C and 106 CFU ml-1 at 7°C. This level of microbial growth in control milk is consistent with data from Ranieri et al (36), who reported that the aerobic plate count of 2% fat fluid milk pasteurized at 72.9°C increased from 102 CFU ml-1 on day 1 postpasteurization to 106 CFU ml-1 on day 21 when stored at 6°C, and Petrus et al (35), who reported a 102 CFU ml-1 increase in 4 days at 4°C. Spoiled milk actually has higher CFUs, and this cut-off level was chosen as it represents bacteria in log-phase growth and anticipates sensory and physical defects (34).…”
Section: Discussionsupporting
confidence: 90%
“…Control milk, therefore, reached cut-off values in less than 1 week, with aerobic microbiota counts of 104 CFU ml-1 when held at 4°C and 106 CFU ml-1 at 7°C. This level of microbial growth in control milk is consistent with data from Ranieri et al (36), who reported that the aerobic plate count of 2% fat fluid milk pasteurized at 72.9°C increased from 102 CFU ml-1 on day 1 postpasteurization to 106 CFU ml-1 on day 21 when stored at 6°C, and Petrus et al (35), who reported a 102 CFU ml-1 increase in 4 days at 4°C. Spoiled milk actually has higher CFUs, and this cut-off level was chosen as it represents bacteria in log-phase growth and anticipates sensory and physical defects (34).…”
Section: Discussionsupporting
confidence: 90%
“…According to Cromie (1991) stability of pasteurized milk is influenced by various factors that include the quality of raw material, pasteurization time, resistant microorganism to pasteurization temperatures particularly psychrotrophics, post pasteurization contaminants and storage temperature. A shelf life of 43,36,8,5, and 3 days for pasteurized milk packaged in HDPE bottles and stored at 2, 4, 9, 14 and 16°C, respectively and for those packaged in LDPE pouch it was estimated to be 37, 35, 7, 3, and 2 days, respectively (Petrus et al 2010). …”
Section: Resultsmentioning
confidence: 99%
“…In the US, the shelf life of fluid milk is between 1 to 3 weeks [14], whereas in Brazil, for example, the range drops to 3–8 days, mainly due to poor cold chain conditions [15]. …”
Section: Introductionmentioning
confidence: 99%